Organizing the Voice of Women: A Study of the Polish and Swedish Women’s Movements’ Adaptation to International Structures - Kirsti Stuvøy (Nordisk Østforum, 2020)
Organizing the Voice of Women: A Study of the Polish and Swedish Women's Movements' Adaptation to International Structures, by Eva Karlberg, is reviewed by Kirsti Stuvøy, Associate Professor, Faculty of Landscape and Society, International Environment and Development Studies (Noragric), Norwegian University of Life Sciences (NMBU).